Kesesuaian pencampuran sediaan obat intra vena di Rumah Sakit PKU Muhammadiyah Wonosari - Chairun Wiedyaningsih; Shalahuddin Al Madury; Rina Mutiara (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: The process of intravenous admixture preparations is one of the stages that require special attention to not affect the quality of the resulting preparations. An aseptic technique is required to maintain the sterility of the product produced and ensure its safety.Objective: To identify the appropriateness of the implementation of intravenous admixture based on guidelines and other standard relevant.Methods: This research was conducted at PKU Muhammadiyah Wonosari Hospital in the October-November 2022 period with 100 samples of intravenous injection preparations, which were directly observed using a checklist sheet which was then analyzed quantitativelyResults: The percentage of suitability for the preparatory stage was 89% in the appropriate category. Most suitability in the preparation stage is the use of disposable masks, which is 97%. The suitability of the IV admixture preparations in this study was 54%. The highest suitability of each assessment item is the highest at the stage of preparing all equipment and materials on the workbench (100%) and All drugs mixed using a compatible solvent (100%). Conclusion: In the preparation process, most of them are in accordance with the referenced standards, but at the intravenous admixture stage, the evenness is still low, so improvements are needed to improve aseptic techniques